Self-reported suicidal ideation among individuals with first episode psychosis and healthy controls: findings from the international multicentre EU-GEI study - Heuschen, Caroline; Bolhuis, K.; Zantvoord, J. B.; Bockting, C. L.; Denys, D. A. J. P.; Lok, A.; Arango, C.; Arrojo, M.; Bernardo, M.; Bobes, J.; Del-Ben, C. M.; Di Forti, M.; et al. (Schizophrenia research, 2024)
Introduction - Suicidal ideation is common among individuals with first episode psychosis (FEP), with prevalence estimates up to 56.5 %. Despite its high prevalence, relatively little is known about how sociodemographic, clinical and/or developmental characteristics contribute to the experience of suicidal ideation in individuals with FEP. - Methods - In this cross-sectional study (FEP n = 551 and controls n = 857), univariate logistic regression analyses were performed to study the associations of sociodemographic, clinical, and developmental factors with suicidal ideation in individuals with FEP as well as controls. Suicidal ideation was assessed using the Community Assessment of Psychic Experiences (CAPE). In addition, multivariate logistic regression analyses were conducted based on a stepwise approach. - Results - In FEP, only depressive symptoms remained significantly associated with suicidal ideation when all correlates were integrated into one model. In the multivariate model in controls, depressive symptoms, positive symptoms, and traumatic childhood experiences were significantly associated with suicidal ideation. - Conclusions - This study showed that depressive symptoms are an important factor relating to suicidal ideation in individuals with FEP, over and above other clinical, sociodemographic, and developmental factors. This underscores the relevance of screening for suicidal ideation in individuals with FEP, and highlights the need for a better understanding of the diagnostic uncertainty and course of mood symptoms in early psychosis. - Limitations - Cross-sectional study design, self-reported questionnaires.
Online veröffentlicht: 4 July 2024
Gesehen am 10.04.2025